Modified Liu-Carter Compression Model for Natural Clays with Various Initial Water Contents - Sen Qian; Jian Shi; Jian-wen Ding (Advances in Civil Engineering)
The initial water content has a significant effect on the compression behaviour of reconstituted clays. This effect has to be considered in the Liu-Carter model to ensure the addition voids ratio only related to soil structure. A modified Liu-Carter compression model is proposed by introducing the empirical equations for reconstituted clays at different initial water contents into the Liu-Carter model. The proposed model is verified against the experimental results from the literature. The simulations by the proposed method are also compared with that by old method where the influence of initial water content is not considered. The results show that the predicted virgin compression curves of natural clays are similar, but the values of b and Δey may be very different.